Green History: Reframing Our Past to Save the Planet. (2nd July 2016) - Jones, Andrea K.
ABSTRACT: History museums sometimes struggle to communicate history's relevance to visitors. By reframing historic interpretation through the lens of environmental sustainability and by developing issue-based exhibits to bridge past and present, Accokeek Foundation (which runs the National Colonial Farm) has made colonial history more meaningful to visitors. This article describes the development of its initiative, Green History, changes made to the general visitor experience, and the creation of a school program, Eco-Explorers: Colonial Time Warp, which has stimulated an increase of student visitation by 48% in two years. Both successes and challenges of making history relevant through the lens of environmental sustainability are discussed.